The Effect of Malocclusion on Kurdish Young Children’s Production of Dental, Labio-Dental and Alveolar Sounds: A Case study - Yousif Othman, Dlakhshan (Journal of College of Education, 2021)
The purpose of the present study is to investigate the effect of malocclusion on the production of dental, labio-dental, and alveolar fricative and stop consonants. To achieve this purpose, Fifteen Kurdish young children ranging in age from 8-12 years old were selected to participate in the current study. They were distributed over three groups according to their bite-block occlusions. The participants were asked to pronounce isolate fricative and stop sounds and words which include target sounds, and their voices were recorded. Later, the patricians’ audio-recordings were analyzed via a software praat analysis (wave form and sound spectrograph). The main conclusion of the study was that the children with malocclusions had difficulties in producing the inter-dental, labiodental, and alveolar sounds properly. In addition, distocclusion, open-bite and extra orally deep-bite malocclusions were more signiﬁcant than other types of malocclusions in affecting target sounds production
Keywords: Malocclusion, Acoustic prosperity, Fricative and affricate, Kurdish young children